2022
DOI: 10.2147/ijn.s343902
|View full text |Cite
|
Sign up to set email alerts
|

iRGD Tumor-Penetrating Peptide-Modified Nano-Delivery System Based on a Marine Sulfated Polysaccharide for Enhanced Anti-Tumor Efficiency Against Breast Cancer

Abstract: Background: Breast cancer is a common malignancy in women. Conventional clinical therapies for breast cancer all display moderate clinical efficacies and limitations. It is urgent to explore the novel and combined therapeutic strategies for breast cancer to meet clinical demand. Methods: An iRGD tumor-penetrating peptide-modified nano-delivery system (denoted as iRGD-PSS@PBAE@JQ1/ORI nanoparticles) based on a marine sulfated polysaccharide was developed by codelivery of JQ1 (BET inhibitor) and oridonin (ORI, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…As a peptide with tumor penetrating activity, iRGD (CRGDK/RGPD/EC) can be used for the surface modification of nanoparticles. Many experimental studies on iRGD have confirmed that its modification in iRGD can improve the targeting and retention of nanoparticles in tumors (Lin et al, 2020;Chen B. et al, 2022). Immune cells in the tumor microenvironment (TME) also influence the aggregation of nanoparticles.…”
Section: Epr Combined With Molecular Markers Enables Nanoparticle Tar...mentioning
confidence: 99%
“…As a peptide with tumor penetrating activity, iRGD (CRGDK/RGPD/EC) can be used for the surface modification of nanoparticles. Many experimental studies on iRGD have confirmed that its modification in iRGD can improve the targeting and retention of nanoparticles in tumors (Lin et al, 2020;Chen B. et al, 2022). Immune cells in the tumor microenvironment (TME) also influence the aggregation of nanoparticles.…”
Section: Epr Combined With Molecular Markers Enables Nanoparticle Tar...mentioning
confidence: 99%
“…The iRGD-PSS@PBAE@JQ1/ORI NPs effectively enhanced tumor targeting due to the tumor-overexpressed 𝛼v𝛽3 integrin receptors; JQ1 and ORI were released from nanoparticles in response to intracellular pH/GSH and achieved remarkable synergistic anti-breast cancer efficiency by reversing PD-L1-mediated immune tolerance, increasing intracellular ROS production, and inhibiting lactic acid secretion. [111] Malignant tumors are usually associated with overexpression of HDAC. A novel nanoplatform (M1-EM-SUCS NPs) was established in which M1 macrophagederived exosome membranes camouflaged mesoporous silicamodified lanthanide-doped upconversion nanoparticles (UCs) loaded with SAHA.…”
Section: Combination Of Epigenetic Therapy and Other Therapiesmentioning
confidence: 99%
“…[124,126] Overexpression of 𝛼v𝛽3 integrin receptors, CD44, and mannose receptors in diverse tumor types (e.g., colorectal cancer, breast cancer, and NSCLC) also provides a potential target for iRGD, HA, or mannose-modified nanoparticulate formulations. [55,95,101,108,111] Furthermore, biomimetic nanoparticles including cell membrane-camouflaged nanoparticles (e.g., homologous cancer cell membranes and PD1-expressing T lymphocyte membrane), [94,102,114,116,117,123] exosome-disguised nanoparticles (e.g., M1-derived exosome), [112] albumin nanoparticles, [114] and lactoferrin nanoparticles, [55] served as novel nanotechnology for targeting tumor cells and regulating the TME in the treatment of breast cancer, colorectal cancer, glioma, melanoma, and lung cancer.…”
Section: Overview Of Targeting Strategymentioning
confidence: 99%
“…to completely destroy cancer and compensate for the poor efficiency of single receptor targeting. 139 , 140 Therefore, investigating the target receptors provides huge potential in further researches and oncological clinical applications including the field of early detection, prognosis prediction, clinical outcome evaluation, and personalized diagnosis and therapies, 141 while great challenges need to be solved with well-designed therapeutic strategy and further proper randomized clinical trials for personalized OSCC therapy.…”
Section: The Future Perspectivesmentioning
confidence: 99%